DIGITALISASI PENGELOLAAN KEUANGAN DAN KESIAPAN IMPLEMENTASI SAK EMKM SEBAGAI UPAYA PENINGKATAN KUALITAS LAPORAN KEUANGAN UMKM - Khairina Nur Izzaty; Grace Tianna Solovida (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the effect of the digitalization process on MSME operations and also the readiness of MSME actors regarding the implementation of SAK EMKM to improve the quality of MSME financial reporting. Respondents who were sampled in this study were 118 small business owners who had run their business processes in a hybrid manner (a combination of online and conventional) in Semarang City, Central Java. The research data was obtained by distributing questionnaires either online using the Google form or in person. The data analysis method used is multiple linear regression analysis using SPSS 26 software. The research results obtained are that the use of information technology and online sales systems as the impact of digitization has a positive influence on the quality of MSME financial reporting. In addition, the dissemination of SAK EMKM information and the readiness and understanding of MSME accounting also has a positive effect on the quality of financial reporting. On the other hand, the high perception of MSME actors towards the applicable accounting standards has not been able to produce quality financial reports, and the online payment system also does not affect the quality of financial reporting.